TINGKAT PENDIDIKAN DAN PEKERJAAN IBU DALAM PEMILIHAN KONTRASEPSI IUD - Lina Darmayanti Bainuan (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2017)
At present the rate of population growth in Indonesia is still high, where every year there are 3-4 million people. Based on BKKBN data, the PPM for IUD KB is 77.7% while the IUD family planning enthusiasts in RS.Assakinah Medika are only 21.42%, this figure is far from the PPM determined by the BKKBN. The tendency of still low use of IUD contraception is likely to be highly related to education and acceptor work. The education of acceptors in receiving information about family planning programs and education factors of a person is very influential in the decision to make family planning. The lower the income, the lower the motivation of acceptors in participating in family planning. The purpose of this study was to describe the Education and Employment of Women in Contraception IUD Selection in Sidoarjo in 2015. Method: This study used a descriptive design, the population in the study was all family planning acceptors in RS.Assakinah Medika Sidoarjo in 2015. Sampling by systematic sampling with a sample of 200 acceptors of IUD KB. Analysis uses frequency tables and cross tabulations. Results: The results of the study, family planning acceptors used IUD KB (20%), acceptors who did not use IUD KB (80%). The majority of those who use family planning are acceptors with high education (28.00%) and working mothers (21.38%). Discussion: one's education and work will influence family planning acceptors in participating in family planning. It is expected that health workers can provide counseling about family planning so that acceptors can choose according to their health conditions and provide communication, information, education to family planning acceptors and prospective family planning acceptors so that they understand correctly about the types, effects of contraception and the benefits of contraception.